2012
DOI: 10.5959/eimj.v4i1.14
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Understandings of Turkish Medical Graduate Students about Nature of Scientific Knowledge, Scientific Method, Characteristics of Scientists and Definition of Science

Abstract: How to cite this article?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…They define science as a "study of the world" by making frequent reference to man. In another study, Koksal and Koksal (2012) showed that medical researchers define science by focusing on study objects such as animals, plants or life. Hence, anthropocentricity might not be the only reason for NOS misunderstandings of definition of science.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They define science as a "study of the world" by making frequent reference to man. In another study, Koksal and Koksal (2012) showed that medical researchers define science by focusing on study objects such as animals, plants or life. Hence, anthropocentricity might not be the only reason for NOS misunderstandings of definition of science.…”
Section: Discussionmentioning
confidence: 99%
“…Learning science might be confused with stereotyped learning of scientists depicted as a quick learning process (e.g. immediate sparkling when something is learnt) in resources or minds when scientists learn about the unknown (Irez, 2009;Koksal & Koksal, 2012;Meyers, 2007). Hence, scientists are depicted as quick learners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations